Evaluation of Roselle (Hibiscus sabdariffa L.) Varietal Responses to Foot and Stem Rot Caused by Phytophthora parasitica var. sabdariffae - , Swathi B, Rajasekhar Y, Sreenivas G, Srinivas Rao M, Sandhya Rani Y, Chitti Babu G (Archives of Current Research International, 2025)
Mesta or Roselle (Hibiscus sabdariffa L.) is one of the most important commercial fibre crops after Cotton and Jute. Foot and stem rot is one of the major devastating diseases affecting mesta plants caused by the fungus Phytophthora parasitica var. sabdariffae. Field trials were conducted at the Agricultural Research Station, Amadalavalasa for two consecutive years during Kharif 2022-23 and 2023-24 to evaluate Advanced Varietal Trial (AVT) entries against foot and stem rot in roselle under sick plot conditions. Same Six set of entries were screened under Advanced Varietal Trial (AVT I) during 2022-23 and Advanced Varietal Trial (AVT II) during 2023-24 against foot and stem rot disease of mesta under field (sick plot) conditions. Each treatment replicated thrice in a randomized block design and Analysis of variance (ANOVA) was carried out on the data to test for differences using MS Excel. In AVT I entries, the disease incidence of foot and stem rot ranged from 23.0% (AHS-340) to 42.3% (AHS-342) and the susceptible checks HS 4288 and AMV 5 recorded disease incidence of 46.1% and 47.6% respectively. Among the six AVT II entries screened under sick plot conditions, foot and stem rot incidence ranged from 24.1% (AHS-340) to 50.6% (AHS-342). The susceptible checks HS 4288 and AMV 5 recorded disease incidence rates of 50.2% and 60.0% respectively.